THE PHENOMENOLOGY OF TA'AWUN IN MUSLIM ECONOMIC EXPERIENCE: A PHILOSOPHICAL STUDY OF COLLECTIVE ECONOMIC CONSCIOUSNESS - Sugeng Riyadi (International Journal of Multidisciplinary Reseach, 2025)
This study investigates the phenomenon of ta'awun (mutual cooperation) within the context of Muslim economic experience through a phenomenological lens. Utilizing a philosophical approach, this research aims to uncover the essence and meaning of the collective economic consciousness underlying ta'awun practices. A qualitative research method, through comprehensive literature review and descriptive analysis, is employed to explore the manifestations of ta'awun, ranging from traditional barter systems to contemporary Islamic finance innovations such as Sharia fintech and crowdfunding. Findings indicate that ta'awun is not merely an economic transaction but an intersubjective experience that shapes a collective consciousness prioritizing solidarity, justice, and sustainability. This study contributes to a deeper understanding of the ethical and philosophical dimensions of Islamic economics, challenging individualistic economic paradigms, and offering a framework for developing more humane and equitable economic models. The collective economic consciousness emerging from ta'awun serves as a foundation for building resilient and prosperous communities.